2022
DOI: 10.3390/nu14040855
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of Dual-Protein Nutrition Differentially Impacts the Formation of Atherosclerosis in ApoE−/− Mice

Abstract: Atherosclerosis (AS) is recognized as the original cause of most cardiovascular and cerebrovascular diseases. The dual-protein (DP) nutrition that consists of soy protein and whey protein is reported to be associated with a reduction in AS; however, the relationship between DP and AS remains ambiguous. Therefore, this study aimed to verify the effect of DP on AS and explore the optimal DP intake to improve AS. ApoE−/− mice were administrated with low- (LDP), middle- (MDP), and high-dose (HDP) DP. The MDP group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Its high nutritional value and bioavailability play an important role in maintaining body health and promoting body growth. Most importantly, the preliminary findings demonstrated that the dual-protein had significant nutritional quality improvement in hematopoietic reconstruction, immune function, muscle level, lipid metabolism, and osteoporosis [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its high nutritional value and bioavailability play an important role in maintaining body health and promoting body growth. Most importantly, the preliminary findings demonstrated that the dual-protein had significant nutritional quality improvement in hematopoietic reconstruction, immune function, muscle level, lipid metabolism, and osteoporosis [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its high nutritional value and bioavailability play important roles in maintaining physical health and promoting body growth. Preliminary findings demonstrated that a dual protein had significant nutritional quality improvement in hematopoietic reconstruction, immune function, muscle level, lipid metabolism, and osteoporosis [9][10][11]. Whey protein isolate (WPI) and soy protein isolate (SPI) are the main animal-plant protein ingredients in dual proteins; both have excellent functional processing properties such as emulsification, gelation and foaming, which are widely used in food processing [12,13].…”
Section: Introductionmentioning
confidence: 99%